THE INFLUENCE OF WORKLOAD, LOCUS OF CONTROL, AND ORGANIZATIONAL CLIMATE ON JOB SATISFACTION OF EMPLOYEES AT PT. NASMOCO PURWOKERTO - Vanda Rizki Kustriani; Hengky Widhiandono; Fatmah Bagis; Alfalisyado Alfalisyado (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
The purpose of this study was to test and analyze the influence of workload variables, locus of control, and organizational climate on job satisfaction of PT Nasmoco Purwokerto employees. This study uses a quantitative approach with a sample consisting of 75 employees of PT Nasmoco Purwokerto obtained through distributing questionnaires. Data analysis was performed using Structural Equation Modeling-Partial Least Square (SEM-PLS). The results showed that there was a negative and significant influence between workload on job satisfaction, with a coefficient value of -0.320 and a p value of 0.001 (0.05). Internal locus of control has a positive and significant influence on job satisfaction, with a coefficient value of 0.468 and a p value of 0.000 (0.05). In addition, organizational climate also has a positive and significant effect on job satisfaction, with a coefficient value of 0.392 and a p value of 0.000 (0.05). In contrast, external locus of control did not show a positive and significant effect on job satisfaction, with a coefficient value of -0.072 and a p value of 0.503 ( 0.05). These results indicate that workload, internal locus of control, and organizational climate have a significant influence on job satisfaction of PT Nasmoco Purwokerto employees, while external locus of control has no significant effect.